Ba2B6O11, a Member of the BaO‐B2O3 Family, Featuring a Layer Framework. Issue 20 (24th June 2015) - Liu, Lili; Yang, Yun; Dong, Xiaoyu; Lei, Chen; Han, Shujuan; Pan, Shilie
Abstract: Ba2 B6 O11, a new member of the BaO‐B2 O3 family, has been found and features a layered structure. The single‐crystal X‐ray structural analysis revealed that Ba2 B6 O11 crystallizes in the monoclinic space group P 21 / c . The parameters of the monoclinic unit cell are a = 9.115(1), b = 7.773(1), c = 12.696(2) Å, β = 100.325(9)°, and Z = 4. The new centrosymmetric alkaline earth metal borate, Ba2 B6 O11, is characterized by a 2D B–O framework composed of the basic building block (B6 O14 ) with the Ba 2+ cations filling the channels formed by the (B6 O14 ) units or located between the (B6 O10 )∞ layers. Ba2 B6 O11 has a short cut‐off edge of 240 nm. Based on a theoretical calculation, it has been proven that Ba2 B6 O11 has a birefringence of 0.04 and a relatively large indirect band gap of 4.94 eV, which is close to the experimental value of 5.17 eV. Its structure is discussed in terms of the B–O framework and dimensional reduction formalism together with the other structures reported in the BaO‐B2 O3 phase diagram. Abstract : Ba2 B6 O11, a new centrosymmetric barium borate, features a layered structure and a wide transmission range from 240 to 2600 nm.